Comparative study of semiconductor TiO2 and noble metal Ag substrates: The differences between chemical enhancement and electromagnetic enhancement in SERS. (24th April 2018) - Jiang, Xin; Chen, Yongliang; Du, Juan; Li, Xiuling; Shen, Yu; Yang, Ming; Han, Xiaoxia; Yang, Libin; Zhao, Bing
Abstract: The differences between electromagnetic enhancement and chemical enhancement in surface‐enhanced Raman scattering (SERS) and their deep insight are very important and valuable for the explanation of spectral behaviors and the practical application of SERS technique. In this work, the typical semiconductor substrate TiO2 nanoparticles and noble‐metal substrate Ag colloid were selected as two representative SERS‐active substrates to investigate the differences between the electromagnetic (EM) mechanism and the charge‐transfer (CT) mechanism using 4‐mercaptobenzoic acid as probe molecule. The 4‐mercaptobenzoic acid molecules on two substrates exhibit the obvious differences in spectral behavior and signal intensity of SERS as well as the detectability, which can be attributed to the essential differences between the EM mechanism and the CT mechanism. The EM enhancement more depends on the behavior of the substrate, which more tends to be nonselective for the adsorbed molecules and their enhancement. The CT enhancement not only depends on the behavior of the substrate but also depends on the behavior of the adsorbed molecule due to the CT between substrate and molecule, which more tends to be selective for the adsorbed molecules and their enhancement. Moreover, it is also proved that the semiconductor (TiO2 ) SERS‐active substrate is characterized by the high stability and the recyclability. Abstract : The typical semiconductor substrate TiO2 nanoparticles and noble‐metal substrate Ag colloid were selected as two representative surface‐enhanced Raman scattering (SERS)‐active substrates to investigate the differences between the electromagnetic mechanism and the charge‐transfer mechanism using 4‐mercaptobenzoic acid as probe molecule. The 4‐mercaptobenzoic acid molecules on two substrates exhibit the obvious differences in spectral behavior and signal intensity of SERS as well as the detectability, which can be attributed to the essential differences between the electromagnetic mechanism and the charge‐transfer mechanism.